Pathological role of angiostatin in heart failure: an endogenous inhibitor of mesenchymal stem-cell activation. Issue 4 (18th December 2008) - Yamahara, K; Min, K D; Tomoike, H; Kangawa, K; Kitamura, S; Nagaya, N
Abstract : Objective: Recently, a clinical trial was initiated to evaluate the efficacy of transendocardial transplantation of autologous bone marrow-derived mesenchymal stem cells (MSC) for the treatment of heart failure (HF). Because some HF patient-derived sera did not induce proliferation of autologous MSC, the present study aimed to elucidate humoral factors in sera that attenuate MSC activation and to investigate the role of these humoral factors in the pathogenesis of HF. Methods and results: Inhibitory effects present in serum were analysed by culturing human MSC with sera from 10 HF patients (FS <25%, BNP >100 pg/ml) and four healthy control subjects. Among the patients, two sera from HF patients showed significant inhibitory activity on MSC proliferation. Protein array and ELISA analysis revealed that these sera contained high levels of angiostatin as well as the active form of matrix metalloproteinase (MMP)-9, which generates angiostatin. Angiostatin significantly inhibited the proliferation and migration of cultured human MSC and increased their apoptosis in a dose-dependent manner. In a rat HF model, serum levels of angiostatin and MMPs increased, but treatment with an MMP inhibitor suppressed these increases. Conclusions: The results suggest that angiostatin, which can attenuate the activity of MSC, might play a role in the progression of HF.